Evaluating library collections and support services for distance learning programme : a study of e-PJJ students’ perceptions of PTAR UiTM, Malaysia / Halimatun Saadiah Roselley and Fuziah Mohd Nadzar - Mohd Nadzar, Fuziah (Faculty of Information Management, 2013)
This study was a descriptive research to determine the distance learning students’ perceptions of library collections and library support services provided by the Perpustakaan Tun Abdul Razak (PTAR) to support the distance learning programme at the Faculty of Information Management, UiTM. Two research questions guided this study: (1) What are the distance learning students’ perceptions on the current PTAR’s collections? and (2) What are the distance learning students’ perceptions on PTAR’s support services for the distance learning programme? A structured survey questionnaire was developed to address these research questions. The questionnaires were administered to 138 distance learning students of the Faculty of Information Management, UiTM during their weekend classes. The findings revealed that most of the respondents were satisfied with the provision of library collections, which indicate that PTAR had been able to meet the needs of distance learning students in terms of its collections. However, this study found that most of the respondents were not satisfied with the library support services they received as distance learning students, especially PTAR’s web OPAC and PTAR’s reference assistance. The investigation into the distance learning students’ perceptions on library collections and support services for distance learning programmes may provide some insights for assessing and improving PTAR’s library services for distance learning programmes in the future.